In memoriam: Annemarie Heywood Died, March 2016 (Journal of Namibian Studies : History Politics Culture, 2016)
Annemarie Johanna Heywood (nee Gaerdes), died on 13th March 2016 in The Roman Catholic Hospital, Windhoek, aged 89.